Science Teachers’ perceptions Regarding STEM Education - Fatima Hashmi, Naheed; Maqsood, Ayesha; Nadeem, Muniza (JSE, 2024)
STEM Education integrates Science, Technology, Engineering, and Mathematics. It emphasizes inquiry-based and student-centered learning, which are necessary 21st-century skills. The main purpose of this study was to examine Secondary school teachers' perceptions of STEM education. The participants of the survey were science teachers with different experiences in District Sargodha. The population was 1119 secondary school science teachers. The sample was selected using cluster sampling and proportionate sampling. The number of respondents in the sample was 300. It was a quantitative descriptive type of research in which a survey was carried out. Data was collected through questionnaires and data were analyzed through descriptive statistics. Key findings were that most of the teachers have a positive perception of STEM education. They considered it important to cope with the challenges of the 21st century. The challenge is the lack of training in STEM. Keeping in view the key findings, it was recommended that STEM education be implemented in private and public schools but there should be a proper curriculum for this. There should be a proper training program to train the teachers about STEM education.